The Boundaries of the Accounting Universe: The Accounting Rules of Selection (Book). - Burns, Thomas J. (The Accounting Review, 1979)
Reviews the book "The Boundaries of the Accounting Universe: The Accounting Rules of Selection," by George H. Sorter.